2018
DOI: 10.1186/s12870-018-1258-9
|View full text |Cite
|
Sign up to set email alerts
|

OsNOA1 functions in a threshold-dependent manner to regulate chloroplast proteins in rice at lower temperatures

Abstract: BackgroundAlthough decreased protein expressions have been observed in NOA1 (Nitric Oxide Associated protein 1) deficient plants, the molecular mechanisms of how NOA1 regulates protein metabolism remain poorly understood. In this study, we have used a global comparative proteomic approach for both OsNOA1 suppression and overexpression transgenic lines under two different temperatures, in combination with physiological and biochemical analyses to explore the regulatory mechanisms of OsNOA1 in rice.ResultsIn OsN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Qinghai Province is located in the Qinghai-Tibet Plateau. The average temperature during crop growth is lower, and the expression level of BnaA02g30310D (GCH-1) in NILs (aa) and ZS11 was more strongly expressed at three stages in the study, especially at the six-leaf stage, which is consistent with the results obtained by He [33,34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Qinghai Province is located in the Qinghai-Tibet Plateau. The average temperature during crop growth is lower, and the expression level of BnaA02g30310D (GCH-1) in NILs (aa) and ZS11 was more strongly expressed at three stages in the study, especially at the six-leaf stage, which is consistent with the results obtained by He [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…Yang et al [33] found that the chlorophyll content decreased with increasing OsNOA1 at a low temperature (22 °C). He [34] suggested that OsNOA1 directly regulates the chloroplast self-coding protein by affecting the function of the chloroplast ribosome and then transmits the signal to the nucleus through the chloroplast retrograde signal pathway mediated by Mg protoporphyrin IX, further affecting the expression of chloroplast protein encoded by the nuclear gene. Qinghai Province is located in the Qinghai-Tibet Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…NO affects photosynthesis and photorespiration in various plants [53,54]. For example, OsNOA1 loss-of-function mutations in rice reduced chlorophyll levels during low temperature [55]. It was also reported that the application of a NO donor, SNP, could enhance the photosynthetic activity and reduce the Chl degradation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [37] found that the chlorophyll content decreased with increasing OsNOA1 at a low temperature (22 °C). He [38] suggested that OsNOA1 directly regulates chloroplast-encoded proteins by affecting the function of the chloroplast ribosome and then transmits a signal to the nucleus through the chloroplast retrograde signaling pathway mediated by Mg protoporphyrin IX, further affecting the expression of chloroplast proteins encoded by the nuclear genes. The location of this study, Qinghai Province, is on the Qinghai-Tibet Plateau, where the average temperature during crop growth is low.…”
Section: Candidate Genes Predictionmentioning
confidence: 99%